Big Data and Business Intelligence in the Public Sector: Implementation and Benefits - Tandilino, Charles; Khaerany, Rizky; Pontoh, Grace T.; Indrijawati, Aini (Jurnal Akuntansi Aktual, 2025)
Purpose: This research aims to map and summarize how the implementation and benefits of big data and business intelligence (BI) leverage the advancements of the digital transformation era applied in the public sector to achieve its objectives. Method: The research method used in this article is Systematic Literature Review (SLR) using 56 published and indexed articles by Scopus and Google Schoolar in the range of 2014-2023. Findings: The results map several important points, namely the implementation and factors that help the effective application of big data and BI in the public sector, as well as the benefits of implementing big data and BI in the public sector. Although the use of big data and BI is very important in policy determination and the provision of public services in the public sector, the literature and guidelines for its use are still very low when compared to the private sector. Originality/Value: The implementation of big data and BI in the public sector needs to be further developed. Some of the research topics in the future that can be developed can focus on the development of implementation frameworks, success factors, and the impact of technology on efficiency, transparency, and decision-making in the public sector, while also providing practical guidance for policymakers practitioners.